Material Selection for Fatigue Resistance in Coal Screening Systems: Finite Element Analysis of HB400 and GS20Mn5 at PT Bukit Asam Tarahan Port - Kiagus A Hadi; Anung Suwito (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Fatigue failure due to impact loads on the CV507 screen coal flow breaker plate has caused operational constraints that hamper coal production at PT. Bukit Asam – Tarahan Harbor. This research aims to determine the optimal material selection for coal flow breaker plates to achieve superior fatigue life and operational safety. HB400 material was selected for its high hardness and wear resistance, suitable for applications experiencing friction and direct coal impact. GS20Mn5 was chosen for its high toughness and superior impact energy absorption capabilities without cracking, particularly under repeated impact loading conditions. Two materials, Hardock (HB400) and GS20Mn5, with thicknesses of 15 mm and 20 mm respectively, were analyzed using static structural and explicit dynamic analysis in ANSYS Workbench 2022 R1 software. Simulation results indicate that the maximum operational impact load is 15.2 kN. The highest maximum Von Mises stress occurred in the Hardock (HB400) material with 15 mm thickness at 2348.3 MPa, with total deformation of 12.139 mm. Increasing thickness by 5 mm in the Hardock (HB400) material reduced stress and total deformation to 1543.3 MPa and 11.476 mm, respectively. GS20Mn5 material with 20 mm thickness demonstrated the longest fatigue life of 8 months compared to Hardock (HB400). This research provides material selection guidelines for coal flow breaker plates, offering significant value for engineering applications and the mining industry.